Acute care of severely frail elderly patients in a CGA-unit is associated with less functional decline than conventional acute care - Ekerstad N (Clinical Interventions in Aging, 2017)
Niklas Ekerstad,1,2 Synneve Dahlin Ivanoff,3 Sten Landahl,4 Göran Östberg,5 Maria Johansson,5 David Andersson,6 Magnus Husberg,2 Jenny Alwin,2 Björn W Karlson7 1Department of Cardiology, NU (NÄL-Uddevalla) Hospital Group, Trollhättan-Uddevalla-Vänersborg, 2Department of Medical and Health Sciences, Division of Health Care Analysis, Linköping University, 3Center of Aging and Health (AGECAP), Section of Health and Rehabilitation, 4Department of Geriatrics, The Sahlgrenska Academy at the University of Gothenburg, Gothenburg, 5Division of Internal and Acute Medicine, NU Hospital Group, Trollhättan-Uddevalla-Vänersborg, 6Department of Management and Engineering, Division of Economics, 7Department of Molecular and Clinical Medicine, Institute of Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden Background: A high percentage of individuals treated in specialized acute care wards are frail and elderly. Our aim was to study whether the acute care of such patients in a comprehensive geriatric assessment (CGA) unit is superior to care in a conventional acute medical care unit when it comes to activities of daily living (ADLs), frailty, and use of municipal help services.Patients and methods: A clinical, prospective, controlled trial with two parallel groups was conducted in a large county hospital in West Sweden and included 408 frail elderly patients, age 75 or older (mean age 85.7 years; 56% female). Patients were assigned to the intervention group (n=206) or control group (n=202). Primary outcome was decline in functional activity ADLs assessed by the ADL Staircase 3 months after discharge from hospital. Secondary outcomes were degree of frailty and use of municipal help services.Results: After adjustment by regression analyses, treatment in a CGA unit was independently associated with lower risk of decline in ADLs [odds ratio (OR) 0.093; 95% confidence interval (CI) 0.052–0.164; P<0.0001], and with a less prevalent increase in the degree of frailty (OR 0.229; 95% CI 0.131–0.400; P<0.0001). When ADLs were classified into three strata (independence, instrumental ADL-dependence, and personal ADL-dependence), changes to a more dependence-associated stratum were less prevalent in the intervention group (OR 0.194; 95% CI 0.085–0.444; P=0.0001). There was no significant difference between the groups in increased use of municipal help services (OR 0.682; 95% CI 0.395–1.178; P=0.170).Conclusion: Acute care of frail elderly patients in a CGA unit was independently associated with lesser loss of functional ability and lesser increase in frailty after 3 months. Keywords: frail elderly, comprehensive geriatric assessment, acute care, functional outcomes